Über den Einfluss von Klima, jüngerer Sedimentation und Bodenprofilentwicklung auf die Savannen Nord-Surinams (Mittelguyana) - Bakker, Jan Pieter (ERDKUNDE, 1954)
From a climatological point of view only an extremely narrow fringe of North Surinam is to be classified as having Köppen’s savanna climate. This coastal belt of beach ridges, however, possesses in most cases ground water conditions and soil profiles of such quality that savanna is not actually formed. Only occasionally does a savanna-like variant of evergreen seasonal forest (Lindemann’s cereus ridge wood) occur. On the other hand in the areas where savanna is found the mean annual rainfall varies between 1952 mm. in the west and 2430 mm. in the east and, following Troll, these areas are to be classified as experiencing tropical rain forest climate with orographic rain derived from the trade winds. It follows therefore that these savannas cannot be exclusively the result of climate. On the whole, the following natural conditions can be considered the causes responsible for the formation of savannas: A. In the districts of geologically recent deposits (For the recent phases of deposition cf. Bakker, Kiel and Müller, 1953):- 1. The occurrence, near the surface, of impermeable or nearly impermeable kaolin horizons due to normal deposition; 2. The formation, in a similar position, of hard pans and clay pans brought into existence in the course of development of the soil profile; 3. The soil wash, which in areas of sedimentary rocks is removing the upper horizons with their favourable structure; as a result, reserves of soil moisture are insufficient for tree growth during the dry season (September, October, November); 4. The existence of deeply incised rivers and creeks which both enable soil wash material to be transported away in these otherwise rather flat areas and also themselves provide space suitable for deposition. Creek valleys are found, which, to a depth of ten metres and more, are filled with very recent, unconsolidated material of soil wash origin. B. On the basal complex rocks of the northern hill country: - 1. The formation of impermeable B-horizons near the surface as a result of soil profile development; 2. The soil wash, resulting in the formation of more or less developed skeletal soils with truncated profiles, which, having kaolin horizons near the surface, during the dry season contain inadequate reserves of soil moisture; 3. The greater variation in relief which makes it possible for soil wash material either to be laid down as colluvial deposits on the valley slopes or as alluvial deposits in the beds of the rivers and creeks, or to be removed altogether. In this way savannas can originate independently of any human influence. However, of a particularly far reaching consequence is the even more pronounced deterioration of the soil profile that takes place as a result of shifting cultivation and burning. This brings about in many cases the prevention of spontaneous re-afforestation and the formation of secondary landscapes of savanna type which, in the same way as natural savannas, may function as foci for a spread of soil wash and an expansion of the savanna area. As an explanation for the occurence of savannas on coarse sands with low clay content, the factor of leaching has recently been used again by Cohen and Van der Eyk. In my opinion, this plays a lesser part in such soils than the greatly reduced supply of ions resulting from destruction of the top soil, rich in humus, and the isolation of the substrata as a consequence of continuing formation of clay pans and hard pans. Taking account of the earlier observations and classifications by Lanjouw, Bakker, Lindemann, Cohen and Van der Eyk, the pedological and other classificatory principles relating to the origin of savannas in North Surinam, as well as the origins of the many types of savannas in general are discussed. Finally the question is put whether perhaps even in those savanna regions which are supposedly the result of climatic conditions, edaphic and human factors have played a more important rôle than hitherto assumed.